HUBUNGAN KOMUNIKASI PERAWAT DALAM PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN DI PUSKESMAS COLOMADU 1 KABUPATEN KARANGANYAR - Anik Suwarni; Dina Mariyana (JURNAL ILMIAH EDUNOMIKA, 2023)
Patient satisfaction toward nurse communication is the level of one's feelings after comparing patients nurses perceived communication with the expectation desired by the patient. Nurses in providing nursing care can not be separated from the nurse communication with patients that can affect patient satisfaction. Interview results are known in 5 patients who received less outpatient good service nurses in part because communication is less friendly to the patient empathy also those with less effective.To determine the relationship between the communication of nurses in health care with patient satisfaction in the health center Colomadu I Karanganyar. This descriptive quantitative research with cross sectional design. Population of 2500 patients, 96 samples were taken by accidental sampling technique. Data analysis techniques used by Kendall Tau correlation analysis: (1) Communication nurses mostly have good communication as many as 48 people (50.0%), (2) patient satisfaction satisfied people mostly belonging to as many as 56 people (58.3%); (3) There is a significant relationship between the communication of nurses in health care with patient satisfaction in the health center Colomadu I Karanganyar (r xy = 0.525> 0.218; p = 0.000